Encouraging Adoption of Protective Behaviors to Mitigate the Spread of COVID-19: Strategies for Behavior Change - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2020)
This rapid expert consultation is intended to help decision makers identify strategies for increasing adherence to protective behaviors that can mitigate the spread of COVID-19. Ultimately, the focus is on increasing knowledge, reducing barriers, and emphasizing efforts that make healthier choices easier and rewarding, to complement communication interventions. It was produced through the Societal Experts Action Network (SEAN), an activity of the National Academies of Sciences, Engineering, and Medicine that is sponsored by the National Science Foundation. SEAN links researchers in the social, behavioral, and economic sciences with decision makers to respond to policy questions arising from the COVID-19 pandemic.
Keywords: Health and Medicine

Evaluating COVID-19-Related Surveillance Measures for Decision-Making - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2022)
As the COVID-19 pandemic has continued to evolve, the types of data available have changed with the identification of new variants, the availability of COVID-19 vaccines, the introduction of new COVID-19 therapeutics, the reopening of the economy, and the relaxing of mitigation measures. Enhanced understanding of these data types can lead to more informed decisions. The latest guidance from the Societal Experts Action Network (SEAN) highlights new and updated COVID-19 data measures and surveillance strategies that decision makers can use to inform policy decisions. This rapid expert consultation was produced by SEAN, an activity of the National Academies of Sciences, Engineering, and Medicine that is sponsored by the National Science Foundation. SEAN links researchers in the social, behavioral, and economic sciences with decision makers to respond to policy questions arising from the COVID-19 pandemic. This project is a collaboration with the National Academies' Standing Committee on Emerging Infectious Diseases and 21st Century Health Threats, which is sponsored by the U.S. Department of Health and Human Services, Office of the Assistant Secretary for Preparedness and Response.
Keywords: Health and Medicine

The Impact of COVID-19 on the Careers of Women in Academic Sciences, Engineering, and Medicine - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2021)
The spring of 2020 marked a change in how almost everyone conducted their personal and professional lives, both within science, technology, engineering, mathematics, and medicine (STEMM) and beyond. The COVID-19 pandemic disrupted global scientific conferences and individual laboratories and required people to find space in their homes from which to work. It blurred the boundaries between work and non-work, infusing ambiguity into everyday activities. While adaptations that allowed people to connect became more common, the evidence available at the end of 2020 suggests that the disruptions caused by the COVID-19 pandemic endangered the engagement, experience, and retention of women in academic STEMM, and may roll back some of the achievement gains made by women in the academy to date. The Impact of COVID-19 on the Careers of Women in Academic Sciences, Engineering, and Medicine identifies, names, and documents how the COVID-19 pandemic disrupted the careers of women in academic STEMM during the initial 9-month period since March 2020 and considers how these disruptions - both positive and negative - might shape future progress for women. This publication builds on the 2020 report Promising Practices for Addressing the Underrepresentation of Women in Science, Engineering, and Medicine to develop a comprehensive understanding of the nuanced ways these disruptions have manifested. The Impact of COVID-19 on the Careers of Women in Academic Sciences, Engineering, and Medicine will inform the academic community as it emerges from the pandemic to mitigate any long-term negative consequences for the continued advancement of women in the academic STEMM workforce and build on the adaptations and opportunities that have emerged.
Keywords: Policy for Science and Technology

Lessons Learned in Health Professions Education During the COVID-19 Pandemic, Part 2: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2022)
The COVID-19 pandemic was arguably the greatest disrupter health professional education (HPE) has ever experienced. To explore how lessons learned from this unprecedented event could inform the future of HPE, the Global Forum on Innovation in Health Professional Education of the National Academies of Sciences, Engineering, and Medicine convened a virtual workshop series in 2020 and 2021. The first workshop focused on identifying challenges faced by educators, administrators, and students amidst the pandemic and how the different stakeholder groups shifted and adapted in response. The second workshop explored how experts from various health professions might respond to hypothetical—but realistic—future world situations impacting HPE. The final two workshops contemplated the future of HPE post-COVID and explored next steps for applying lessons learned from the workshop series to allow educators to test and evaluate educational innovations in real time. This Proceedings of a Workshop summarizes discussions from the second, third, and fourth workshops in this series.
Keywords: Health and Medicine

Rapid Expert Consultation on SARS-CoV-2 Survival in Relation to Temperature and Humidity and Potential for Seasonality for the COVID-19 Pandemic (April 7, 2020) - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2020)
This rapid expert consultation responds to a request from the Office of Science and Technology Policy (OSTP) concerning survival of the SARS-CoV2 virus in relation to temperature and humidity and potential for seasonal reduction and resurgence in cases. The National Academies of Sciences, Engineering, and Medicine convened a standing committee of experts to help inform OSTP on critical science and policy issues related to emerging infectious diseases and other public health threats. The standing committee includes members with expertise in emerging infectious diseases, public health, public health preparedness and response, biological sciences, clinical care and crisis standards of care, risk communication, and regulatory issues.
Keywords: Health and Medicine

Mental Health and Substance Use Disorders in the Era of COVID-19: The Impact of the Pandemic on Communities of Color: Proceedings of a Workshop—in Brief - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2021)
The Forum on Mental Health and Substance Use Disorders of the National Academies of Sciences, Engineering, and Medicine hosted a virtual workshop, Mental Health and Substance Use Disorders in the Era of COVID-19: With a Special Focus on the Impact of the Pandemic on Communities of Color, on November 23, December 3 and 14, 2020. The workshop featured invited speakers and discussions that addressed how the coronavirus disease 2019 (COVID-19) pandemic has influenced (1) mental health and substance use disorders (SUDs); (2) changes in access to health care and delivery of services for people with mental health disorders and SUDs; and (3) the mental health well-being of the health care workforce - each with a particular focus on the impact of the pandemic on communities of color and how the pandemic has created, revealed, and exacerbated longstanding racial and ethnic disparities in behavioral health care. This Proceedings of a Workshop - in Brief summarizes the presentations and discussions that occurred at the workshop.
Keywords: Health and Medicine

Lessons Learned from the COVID-19 Pandemic to Improve Diagnosis: Proceedings of a Workshop–in Brief - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2022)
On January 14, 2022, the Board on Health Care Services of the National Academies of Sciences, Engineering, and Medicine hosted a virtual workshop focused on examining changes to diagnostic paradigms in response to the COVID-19 pandemic and considering the lessons learned and opportunities for improving diagnosis within the U.S. health care system. The workshop highlighted the pandemic's impact on diagnostic pathways, the exacerbation of inequities, diagnostic responsibilities for public health, and the novel diagnostic strategies and tools that have been developed since COVID-19 emerged. This workshop was the fourth in a series on diagnostic excellence funded by the Gordon and Betty Moore Foundation. This Proceedings of a Workshop-in Brief highlights the presentations and discussions that occurred at the workshop.
Keywords: Health and Medicine

Emerging Viral Diseases: The One Health Connection: Workshop Summary - Institute of Medicine (The National Academies Press, 2015)
In the past half century, deadly disease outbreaks caused by novel viruses of animal origin - Nipah virus in Malaysia, Hendra virus in Australia, Hantavirus in the United States, Ebola virus in Africa, along with HIV (human immunodeficiency virus), several influenza subtypes, and the SARS (sudden acute respiratory syndrome) and MERS (Middle East respiratory syndrome) coronaviruses - have underscored the urgency of understanding factors influencing viral disease emergence and spread. Emerging Viral Diseases is the summary of a public workshop hosted in March 2014 to examine factors driving the appearance, establishment, and spread of emerging, re-emerging and novel viral diseases; the global health and economic impacts of recently emerging and novel viral diseases in humans; and the scientific and policy approaches to improving domestic and international capacity to detect and respond to global outbreaks of infectious disease. This report is a record of the presentations and discussion of the event.
Keywords: Health and Medicine

Stronger Food and Drug Regulatory Systems Abroad - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2020)
Ensuring the safety of food and the quality and safety of medicines in a country is an important role of government, made more complicated by global manufacturing and international trade. By recent estimates, unsafe food kills over 400,000 people a year, a third of them children under 5, mostly in low- and middle-income countries; every year poor quality medicines cause about 70,000 excess deaths from childhood pneumonia and roughly 8,500 to 20,000 malaria deaths in sub-Saharan Africa alone. The Federal Drug Administration (FDA) Office of Global Policy and Strategy is charged with improving capacity of the agency's foreign counterpart offices and increasing understanding of the importance of regulatory systems for public health, development, and trade. At the request of the FDA, this study sets out a strategy to support good quality, wholesome food and safe, effective medical products around the world. Its goal is to build on the momentum for strengthening regulatory systems and to set a course for sustainability and continued progress. The 2012 report Ensuring Safe Food and Medical Products Through Stronger Regulatory Systems Abroad outlined strategies to secure international supply chains, emphasized capacity building and support for surveillance in low- and middle-income countries, and explored ways to facilitate work sharing among food and medical product regulatory agencies. This new study assess progress made and the current regulatory landscape.
Keywords: Food and Nutrition; Health and Medicine

Critical Findings on COVID-19: Select Publications from the National Academies of Sciences, Engineering, and Medicine - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2021)
For more than 150 years, the National Academies of Sciences, Engineering, and Medicine have issued reports detailing leading research on public health and infectious disease. In response to the global outbreak of COVID-19 in 2020, the National Academies has continued this work by issuing publications related to disease transmission, preventative measures, vaccinations, and more that can inform the public response to the pandemic. Critical Findings on COVID-19 includes summaries and highlights of many of our key publications on COVID-19, including consensus study reports, workshop and webinar proceedings, and rapid expert consultations.
Keywords: Health and Medicine

Rapid Expert Consultation on Critical Federal Capabilities Needed to Evaluate Real-World Safety, Effectiveness, and Equitable Distribution and Use of Medical Countermeasures During a Public Health Emergency - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2022)
The COVID-19 pandemic has highlighted the importance of having access to real-world data and evidence to monitor and assess medical countermeasure (MCM) use and performance so policy makers can make more effective and rapid public health decisions, protect population health, and save lives. During public health emergencies, the use of MCMs, such as therapeutics, vaccines, and diagnostics, can be made available to the public under a range of regulatory access mechanisms. This Rapid Expert Consultation was produced by individual members of the Standing Committee for CDC Center for Preparedness and Response. Its aim is to review and propose modifications to an initial draft list of critical federal capabilities presented by the Centers for Disease Control and Prevention and the U.S. Food and Drug Administration that are needed to evaluate real-world safety, effectiveness, equitable distribution, access, and use of MCMs during a public health emergency. This effort draws from expert input, published literature, and lessons learned from previous public health emergencies, as well as the ongoing COVID-19 pandemic.
Keywords: Health and Medicine

Partnerships for Equitable Pandemic Response and Recovery - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2023)
The COVID-19 pandemic had a disproportionate impact on historically marginalized communities—including Black, Latino, and low-income individuals, as well as older adults, and people with chronic health conditions or disabilities. As transit agencies build toward recovery and rethink or reimagine their operations, they might consider grounding their decision-making in equity principles. The TRB Transit Cooperative Research Program's TCRP Synthesis 167: Partnerships for Equitable Pandemic Response and Recovery identifies how transit agencies were able to quickly pivot during the pandemic to deploy resources for other temporary “incidental uses” and respond to the need for essential services. Through these incidental uses of vehicles and facilities, public transit agencies across the country kept workers actively employed while expanding equitable access in unprecedented ways.
Keywords: Transportation and Infrastructure

Crisis Standards of Care: A Systems Framework for Catastrophic Disaster Response: Volume 1: Introduction and CSC Framework - Institute of Medicine (The National Academies Press, 2012)
Catastrophic disasters occurring in 2011 in the United States and worldwide—from the tornado in Joplin, Missouri, to the earthquake and tsunami in Japan, to the earthquake in New Zealand—have demonstrated that even prepared communities can be overwhelmed. In 2009, at the height of the influenza A (H1N1) pandemic, the Assistant Secretary for Preparedness and Response at the Department of Health and Human Services, along with the Department of Veterans Affairs and the National Highway Traffic Safety Administration, asked the Institute of Medicine (IOM) to convene a committee of experts to develop national guidance for use by state and local public health officials and health-sector agencies and institutions in establishing and implementing standards of care that should apply in disaster situations-both naturally occurring and man-made-under conditions of scarce resources. Building on the work of phase one (which is described in IOM's 2009 letter report, Guidance for Establishing Crisis Standards of Care for Use in Disaster Situations), the committee developed detailed templates enumerating the functions and tasks of the key stakeholder groups involved in crisis standards of care (CSC) planning, implementation, and public engagement-state and local governments, emergency medical services (EMS), hospitals and acute care facilities, and out-of-hospital and alternate care systems. Crisis Standards of Care provides a framework for a systems approach to the development and implementation of CSC plans, and addresses the legal issues and the ethical, palliative care, and mental health issues that agencies and organizations at each level of a disaster response should address. Please note: this report is not intended to be a detailed guide to emergency preparedness or disaster response. What is described in this report is an extrapolation of existing incident management practices and principles. Crisis Standards of Care is a seven-volume set: Volume 1 provides an overview; Volume 2 pertains to state and local governments; Volume 3 pertains to emergency medical services; Volume 4 pertains to hospitals and acute care facilities; Volume 5 pertains to out-of-hospital care and alternate care systems; Volume 6 contains a public engagement toolkit; and Volume 7 contains appendixes with additional resources.
Keywords: Health and Medicine; Conflict and Security Issues

Long COVID: Examining Long-Term Health Effects of COVID-19 and Implications for the Social Security Administration: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2022)
'Long COVID' refers to the wide range of long-lasting symptoms experienced by some patients after a SARS-CoV-2 infection. The most common symptoms include fatigue, headache, brain fog, shortness of breath, hair loss, and pain. At this time, there are many knowledge gaps related to Long COVID, including the prevalence of the condition, the impact of the symptoms on survivors' ability to function, and the long-term course of the condition. While many individuals with Long COVID recover within one year, others experience little or no decrease in symptom severity over time. Long COVID symptoms can affect a person's ability to work and otherwise function in daily life, so people with the condition may need to utilize programs such as Social Security Disability Insurance (SSDI) and the Supplemental Security Income Program (SSI). The Social Security Administration (SSA), which administers both of these programs, requested that the National Academies of Sciences, Engineering, and Medicine host a public workshop to discuss research into the long-term health effects of COVID-19, their impacts on individuals and populations, and how the SSDI and SSI programs can support individuals who suffer disability as a result of Long COVID. This publication summarizes the presentation and discussion of the workshop.
Keywords: Health and Medicine

Rental Eviction and the COVID-19 Pandemic: Averting a Looming Crisis - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2022)
As the federal moratorium on rental eviction is set to expire on July 31st, 2021, actionable guidance is urgently needed on how to ensure that renters can stay in their homes and housing aid reaches the communities that need it most. This report from the National Academies of Sciences, Engineering, and Medicine recommends that the Executive Office of the President of the United States should consider establishing a task force to prevent rental evictions and mitigate housing instability caused by the pandemic. Rental Eviction and the COVID-19 Pandemic: Averting a Looming Crisis recommends actions to be taken both urgently and over the next three years aimed at addressing the immediate crisis as well as long-standing needs related to housing choice, affordability, and security across the United States. These include: building on existing social programs that support those struggling with poverty and housing instability; efficiently channeling emergency relief to renters and landlords; increasing the availability of housing choice vouchers; reforming unemployment insurance; and reducing discriminatory practices and systemic inequities.
Keywords: Health and Medicine; Behavioral and Social Sciences

Developing an Airport Communicable Disease Response Plan: Guide and Template - Transportation Research Board; National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2024)
As air travel continues to increase worldwide, threats from communicable disease transmission via air travel remains a top public health concern. Airports can serve as a setting for potential community spread while simultaneously, communicable diseases can adversely impact airport operations.ACRP Web-Only Document 57: Developing an Airport Communicable Disease Response Plan: Guide and Template, from TRB's Airport Cooperative Research Program, provides airport operators with the fundamental information needed to understand communicable diseases and their intersection with airports, an understanding of the range of factors that influence communicable disease incidents in airport contexts, and detailed actions that airport practitioners can consider to develop and implement an airport communicable disease response plan.
Keywords: Transportation and Infrastructure

Big Data and Analytics for Infectious Disease Research, Operations, and Policy: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2016)
With the amount of data in the world exploding, big data could generate significant value in the field of infectious disease. The increased use of social media provides an opportunity to improve public health surveillance systems and to develop predictive models. Advances in machine learning and crowdsourcing may also offer the possibility to gather information about disease dynamics, such as contact patterns and the impact of the social environment. New, rapid, point-of-care diagnostics may make it possible to capture not only diagnostic information but also other potentially epidemiologically relevant information in real time. With a wide range of data available for analysis, decision-making and policy-making processes could be improved. While there are many opportunities for big data to be used for infectious disease research, operations, and policy, many challenges remain before it is possible to capture the full potential of big data. In order to explore some of the opportunities and issues associated with the scientific, policy, and operational aspects of big data in relation to microbial threats and public health, the National Academies of Sciences, Engineering, and Medicine convened a workshop in May 2016. Participants discussed a range of topics including preventing, detecting, and responding to infectious disease threats using big data and related analytics; varieties of data (including demographic, geospatial, behavioral, syndromic, and laboratory) and their broader applications; means to improve their collection, processing, utility, and validation; and approaches that can be learned from other sectors to inform big data strategies for infectious disease research, operations, and policy. This publication summarizes the presentations and discussions from the workshop.
Keywords: Health and Medicine; Math, Chemistry, and Physics; Surveys and Statistics

Building Communication Capacity to Counter Infectious Disease Threats: Proceedings of a Workshop - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2017)
Building communication capacity is a critical piece of preparing for, detecting, and responding to infectious disease threats. The International Health Regulations (IHR) establish risk communication—the real-time exchange of information, advice, and opinions between experts or officials and people who face a threat to their survival, health, and economic or social well-being—as a core capacity that World Health Organization member states must fulfill to strengthen the fight against these threats. Despite global recognition of the importance of complying with IHR, 67 percent of signatory countries report themselves as not compliant. By investing in communication capacity, public health and government officials and civil society organizations facing health crises would be prepared to provide advice, information, and reassurance to the public as well as to rapidly develop messages and community engagement activities that are coordinated and take into account social and behavioral dynamics among all sectors. To learn about current national and international efforts to develop the capacity to communicate effectively during times of infectious disease outbreaks, and to explore gaps in the research agenda that may help address communication needs to advance the field, the Forum on Microbial Threats of the National Academies of Sciences, Engineering, and Medicine convened a 1.5 day workshop on December 13 and 14, 2016, in Washington, DC. Participants reviewed progress and needs in strengthening communication capacity for dealing with infectious disease threats for both outbreaks and routine challenges in the United States and abroad. This publication summarizes the presentations and discussions from the workshop.
Keywords: Health and Medicine

Quarantine Stations at Ports of Entry: Protecting the Public's Health - Institute of Medicine (The National Academies Press, 2006)
To mitigate the risks posed by microbial threats of public health significance originating abroad, the Centers for Disease Control and Prevention (CDC) places small groups of staff at major U.S. airports. These staff, their offices, and their patient isolation rooms constitute quarantine stations, which are run by CDC's Division of Global Migration and Quarantine (DGMQ). Congress began to allocate funds in fiscal 2003 for the establishment of new quarantine stations at 17 major U.S. ports of entry that comprise airports, seaports, and land-border crossings. In a significant departure from the recent past, both the preexisting 8 quarantine stations and the new 17 are expected to play an active, anticipatory role in nationwide biosurveillance. Consequently, DGMQ asked the Institute of Medicine (IOM) to convene an expert committee to assess the present CDC quarantine stations and recommend how they should evolve to meet the challenges posed by microbial threats at the nation's gateways. DGMQ specifically requested "an assessment of the role of the federal quarantine stations, given the changes in the global environment including large increases in international travel, threats posed by bioterrorism and emerging infections, and the movement of animals and cargo." To conduct this assessment and provide recommendations, IOM convened, in October 2004, the Committee on Measures to Enhance the Effectiveness of the CDC Quarantine Station Expansion Plan for U.S. Ports of Entry. At the sponsor's request, the committee released the interim letter report Human Resources at U.S. Ports of Entry to Protect the Public's Health in January 2005 to provide preliminary suggestions for the priority functions of a modern quarantine station, the competences necessary to carry out those functions, and the types of health professionals who have the requisite competences (Appendix A). This, the committee's final report, assesses the present role of the CDC quarantine stations and articulates a vision of their future role as a public health intervention.
Keywords: Health and Medicine; Transportation and Infrastructure

Reusable Elastomeric Respirators in Health Care: Considerations for Routine and Surge Use - National Academies of Sciences, Engineering, and Medicine (The National Academies Press, 2019)
Protecting the health and safety of health care workers is vital to the health of each of us. Preparing for and responding to a future influenza pandemic or to a sustained outbreak of an airborne transmissible disease requires a high-level commitment to respiratory protection for health care workers across the wide range of settings in which they work and the jobs that they perform. Keeping health care workers healthy is an ethical commitment both in terms of addressing the occupational risks faced by health care workers and of providing for the continuity of patient care and services needed to maintain the health of individuals and communities. During a public health emergency, challenges will arise concerning the availability of respiratory protective devices (i.e., respirators). Reusable respirators (specifically, reusable half-facepiece elastomeric respirators) are the standard respiratory protection device used in many industries, and they provide an option for use in health care that has to date not been fully explored. The durability and reusability of elastomeric respirators make them desirable for stockpiling for emergencies, where the need for large volumes of respirators can be anticipated. However, they are used infrequently in health care. Reusable Elastomeric Respirators in Health Care explores the potential for the use of elastomeric respirators in the U.S. health care system with a focus on the economic, policy, and implementation challenges and opportunities. This report examines the practicability of elastomeric use in health care on a routine basis and during an influenza pandemic or other large aerosol-transmissible outbreak, when demand for respiratory protective devices by U.S. health care personnel may be larger than domestic supplies. The report also addresses the issues regarding emergency stockpile management of elastomeric respiratory protective devices.
Keywords: Health and Medicine